Exosomes derived from miR-188-3p-modified adipose-derived mesenchymal stem cells protect Parkinson's disease - Qiang Li; Zihao Wang; Hao Xing; Yu Wang; Yi Guo (Elsevier, 2021)
Parkinson's disease (PD) is the second-most common neurodegenerative disease after Alzheimer's disease. The most important pathological feature of PD is the irreversible damage of dopamine neurons, which is related to autophagy and neuroinflammation in the substantia nigra. Previous studies found that the activation of NAcht Leucine-rich repeat Protein 3 (NLRP3) inflammasome/pyroptosis and cell division protein kinase 5 (CDK5)-mediated autophagy played an important role in PD. Bioinformatics analyses further predicted that microRNA (miR)-188-3p potentially targets NLRP3 and CDK5. Adipose-derived stem cell (ADSC)-derived exosomes were found to be excellent vectors for genetic therapy. We assessed the levels of injury, autophagy, and inflammasomes in 1-methyl-4-phenyl-1,2,4,5-tetrahydropyridine (MPTP)-induced PD mice models and neurotoxin 1-methyl-4-phenylpyridinium (MPP+)-induced cell models after treating them with miR-188-3p-enriched exosomes. miR-188-3p-enriched exosome treatment suppressed autophagy and pyroptosis, whereas increased proliferation via targeting CDK5 and NLRP3 in mice and MN9D cells. It was revealed that mir-188-3p could be a new therapeutic target for curing PD patients.